Questioning in writing center tutorials - Calle Arango, Lina (Íkala, Revista de Lenguaje y Cultura, 2019)
Much of the research on tutoring in writing centers has shown that the relation-ship established between tutor and tutee is decisive as to whether or not the true goal of writing centers is met. That since the late second half of the twentieth century was determined as the need to work on the communicative skills of the individual, and no longer on the product itself. However, within this discussion, little space has been explicitly granted to the potential use of the question in the tutorials. In view of the above, the present theoretical text highlights the impor-tance of using the question as a key tool to encourage analysis and reflection, and highlights the importance of addressing it explicitly in the preparation of tutors, specifically those who participate of the writing centers.